No-Brand Quality Goods: A Study on Purchase Intention of Consumer Behavior in Furniture Retail Industry - Sa Nan Hu; Guan Jie Huang; Tian En Huang; Zhi Qun Huang; Sunny Sunny (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
With the continuous diversification of product types and styles in the market, MUJI, as an established company in the furniture retail industry, has always had a place in the home furnishing retail industry. This study aims to investigate Chinese and Malaysian consumers' purchase intentions towards MUJI products, focusing on five key factors: (1) wide product range, (2) perceived product quality, (3) perceived product price, (4) design style, and (5) brand awareness. To achieve this objective, a quantitative analysis approach was adopted, employing five hypotheses derived from the research objectives. The questionnaire design was structured based on the Richter scale, and data analysis was conducted using SPSS version 23. Through analysis, it was found that perceived product quality and design style have a significant positive impact on purchase intention. Meanwhile, wide range of products, perceived product price, and brand awareness id not demonstrate notable impacts on purchase intent. This research can provide some new references in investigating the purchase intention of consumers in the furniture market. It can also provide some reference opinions for companies in this industry.